Velocity Errors Associated with Application of Inertial Methods for Detecting Rail Surface Short-Wavelength Irregularities - A. V. Bolshakova; A. M. Boronahin; D. Yu. Larionov; L. N. Podgornaya; A. N. Tkachenko; R. V. Shalymov; E. D. Churyaev (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Efficient operation of a system for measuring rail surface short-wavelength irregularities depends on evaluation of the signal length with respect to travelled distances, i.e., the standard maximum defect length and the distance between the wheels of a car bogie. When recording an accelerometer signal with respect to time due to the effect of velocity, the signal length corresponding to these spatially constant distances will vary.Aim. Development of an algorithm for determining rail running surface defects using the data obtained by accelerometers mounted on the axle boxes of a car bogie under their not equidistant spatial record.Materials and methods. The data obtained when passing a laboratory car equipped with a system for measuring short-wavelength irregularities was used. The search and determination of irregularity parameters was carried out by an inertial method. The methods of normalization and correlation analysis were used.Results. An algorithm for determining rail running surface defects based on an inertial method was developed, considering the spatial non-equidistance of the signal. The implemented correlation analysis allows compensation of high-velocity errors when determining the defects. In the considered example, the relative error equaled 0.4 %. Compensation of velocity errors reduces the probability of type I errors in defect determination.Conclusion. The developed algorithm considers velocity errors associated with the application of inertial methods for detecting short-wavelength irregularities. The implementation of correlation analysis reduces the probability of type I errors when determining rail running surface defects.